Sosialisasi Panduan Praktis Pembayaran Pajak Kendaraan Bermotor Secara Online Melalui Aplikasi Signal - Era Lusiana Sianipar; Jusuf Leiwakabessy; Sherly Lewerissa; Audrey Leiwakabessy (Lembaga Pengembangan Kinerja Dosen, 2024)
One important component in the tax structure that provides revenue for the state is motor vehicle tax compliance. Tax sanctions, taxpayer awareness, tax expertise, and other factors can have an impact on motor vehicle tax compliance. For Latta Village residents, online vehicle tax payments using the Signal application are a simpler and more effective option. However, a small proportion of local residents are unable to utilize the application. Thus, this study aims to determine the impact of socialization on Latta Village community compliance in the procedure for paying motor vehicle taxes online through the Signal application, as well as to assist the community in paying motor vehicle taxes online without having to come and queue at Samsat.